The impact of rule (No Harm No Foul) on relevant rulings to the epidemic - Alfayez, Reem Fayez (Journal of Islamic Sciences, 2022)
The research aims to define the concept of the epidemic and its influential control in the legal rulings, and to highlight the impact of the rule of no harm and no harm and the rules that fall under it on the jurisprudence provisions related to the affairs of people in general at the time of the spread of epidemics, and this research is based on the applied descriptive approach, in which extrapolation is done The rules of harm related to epidemics, and the collection of jurisprudential applications related to these rules: - It is forbidden for a person infected with an epidemic to mix with people and witnesses of their meetings, in order to prevent the spread of the epidemic according to the rule of neither harm nor harm. - The ruler may impose stone, legalize Hajj and Umrah, and prevent people from meeting in the time of the epidemic, according to the rule of harm to be paid as much as possible. - In the time of the epidemic, what were binding contracts becomes permissible, so the lease contract for the affected tenant may be terminated, according to the rule of warding off corruption that takes precedence over bringing interest.